PENGARUH BELANJA PEMERINTAH DAERAH TERHADAP KEMISKINAN DAN PENGANGGURAN DI KOTA BATU TAHUN 2017-2020 - Linda Wulandari; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The purpose of this study is to determine the effect of government spending on poverty and unemployment in Batu City from 2017 to 2020. The type of research method used is quantitative research using simple linear regression consisting of classical assumption tests and hypothesis testing and processed with SPSS 16.0. The results of this study indicate that government spending has a significant effect on poverty and government spending also affects unemployment in Batu City in 2017 – 2020.Keywords: Regional Expenditure, Poverty, Unemployment